Unemployment, Job Vacancy And Beveridge Curve In Malaysia, Singapore And The Philippines - Subramaniam, Thirunaukarasu (2007)

(untitled)
The macroeconomic objectives of an economy are maintaining a high economic growth, full employment, price stability, and balance of payments stability. As full employment or low unemployment is one of the objective of Malaysia, Singapore and the Philippines economy, this research will shed some light on how this objective can be achieved. The order of integration is first determined by using various unit root tests namely ADF Test and PP Test. Next, the appropriate cointegration method is used based on the order of integration. The estimation procedure employed in this study is Bounds Test Approach of ARDL-UECM popularised by Pesaran (2001). The Bounds Test of ARDL-UECM shows that Malaysia, Singapore and the Philippines display a steady state long-run equilibrium among unemployment and macroeconomic variables. The analysis using ARDL-UECM Approach displays a negative relationship for Malaysia between unemployment and job vacancy. In contrast, for Singapore and the Philippines, a positive relationship exist between unemployment and job vacancy. Using ARDL-UECM Approach, for Malaysia, job vacancy rate, economic growth, and foreign direct investment are found to be important variables that determines unemployment. For Singapore, variables that are deemed important in determination of unemployment are economic growth and foreign direct investment but for the Philippines, government spending are found to be important. Several conclusions can be derived from this study. Firstly, only Malaysia seems to have fulfilled the Theory of Beveridge Curve. Both Singapore and the Philippines does not fulfill the Theory of Beveridge Curve. Secondly, FDI still plays a major role in reducing unemployment in Malaysia and Singapore but not in the Philippines. Thirdly, the government sector does not have any impact on unemployment in both Malaysia and Singapore but not in the Philippines.